(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Rasipuram Krishnaswami Iyer Narayanaswami was the embodiment of exploratory writing in India. His novels have a bi-social standpoint in which the contention between the antiquated Indian conventions with its qualities on the one side and present day western qualities on the opposite side were self-evident. He had empathetic frame of mind towards ladies however he was moderate in standpoint and personality. His first Sahitya Akademi Award winning novel The Guide is the spiritual odyssey of a human world. The three noteworthy characters Marco, Rosie and Raju were worried about the restoration of local Indian undying confidence in God and respectability. Rosie exemplifies an Indian lady wavering among convention and innovation yet she is very fruitful stylishly, actually and socially in her moving. This paper manages the rise of a novel lady from being a humble woman to an independent lady, as uncovered through the character Rosie. It is likewise an endeavor to evaluate how successfully the novel shows and treats the difference between the East– West subject, an enduring one in Indo-Anglian fiction. In this paper we write about the emergence of Writer R. K. narayan’s as an author.